Student’s Mathematical Communication Skill Based on The Assimilation and Accommodation Framework - Syukma Netti; Khairul Khairul; Puspa Amelia (SAINTIS Publishing, 2019)
The objective of this study was to describe the mathematical communication skill of junior high school students to solve mathematical problem using an assimilation and accomodation framework. This study use qualitative research method. The research data were obtained by giving a mathematical problem to 7th grade students of SMPN 40 Padang, West Sumatera. Methods use for data collection, were test, think aloud and interview. Data that had been collected were analyzed using an assimilation and accommodation framework. Based on data analysis, it was found that were three forms of student’s mathematical communication skill, namely (1) pseudo mathematical communication skill, (2) Inappropriate pseudo mathematical communication skill, and (3) imitation mathematical communication skill.